Codes of Conduct and Standard Setting in the Forest Sector: Constructing Markets for Democracy? - Overdevest, Christine (Relations industrielles / Industrial Relations, 2004)
In an age of globalization, there is a growing perception that state regulatory instruments may be an inadequate means of regulating firm conduct. Increasingly, scholars are evaluating how corporate codes of conduct may operate as regulatory mechanisms. This article examines competing codes of conduct in the forest sector. Through a detailed case study of code adoption, innovation, and diffusion in the forest sector, focusing on mechanisms of vertical, horizontal and competitive diffusion, it is found that non-governmental organization (NGO) codes have placed competitive pressure to adopt higher standards on competing schemes. However, NGO schemes have been limited in constructing fluid markets for their own goods. The article examines which strategies for codes regimes are most likely to diffuse high standards throughout contemporary markets.